2010
DOI: 10.1085/jgp.201010450
|View full text |Cite
|
Sign up to set email alerts
|

Modification of hERG1 channel gating by Cd2+

Abstract: Each of the four subunits in a voltage-gated potassium channel has a voltage sensor domain (VSD) that is formed by four transmembrane helical segments (S1–S4). In response to changes in membrane potential, intramembrane displacement of basic residues in S4 produces a gating current. As S4 moves through the membrane, its basic residues also form sequential electrostatic interactions with acidic residues in immobile regions of the S2 and S3 segments. Transition metal cations interact with these same acidic resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 47 publications
5
32
0
Order By: Relevance
“…This observation demonstrates that voltage sensor return is less energetically favorable than pore closure upon repolarization and demonstrates the important role for voltage sensor relaxation is stabilizing the hERG activated voltage sensor and limiting its return. This finding is consistent with a previous observation of the dissociation between voltage sensor return and pore closure caused by a pharmacological activator compound (29). Furthermore, our data also provide supporting functional evidence for the recent cryo-EM structural prediction of the related eag channel, which captures the channel in a state in which the pore gate is closed, but the voltage sensor is in the activated configuration (6).…”
Section: Characterization Of Mode-shift Behavior In Herg Channelssupporting
confidence: 92%
See 1 more Smart Citation
“…This observation demonstrates that voltage sensor return is less energetically favorable than pore closure upon repolarization and demonstrates the important role for voltage sensor relaxation is stabilizing the hERG activated voltage sensor and limiting its return. This finding is consistent with a previous observation of the dissociation between voltage sensor return and pore closure caused by a pharmacological activator compound (29). Furthermore, our data also provide supporting functional evidence for the recent cryo-EM structural prediction of the related eag channel, which captures the channel in a state in which the pore gate is closed, but the voltage sensor is in the activated configuration (6).…”
Section: Characterization Of Mode-shift Behavior In Herg Channelssupporting
confidence: 92%
“…Data were fitted to a double exponential function (n ¼ 6, 5, and 4, respectively). step depolarization to þ60 mV, which highlights the complex kinetics associated with charge transit across the membrane as has been reported previously in these channels (11,(28)(29)(30)(31). Both on-and off-gating currents display pronounced fast and slow phases of decay.…”
Section: Resultssupporting
confidence: 72%
“…Although our current findings indicate that differential sensitivity to the allosteric effects of RPR on channel gating can be swapped between hERG1 and rERG2 by mutating the few key nonconserved residues in the C-linker, the structural basis of RPR-induced slowing of hERG1 deactivation remains elusive. We previously reported that RPR has no effect on the kinetics, magnitude, or voltage dependence of hERG1 gating currents (Abbruzzese et al, 2010), indicating that the compound dissociates movement of the voltage sensor domain from the opening and closing of the activation gate. RPR could directly or by an allosteric mechanism stabilize the association between the PAS cap and the C-linker or interfere with the coupling between the S4/S5 linkers and the C-terminal region of the S6 segments (Ferrer et al, 2006).…”
Section: Rpr Has Differential Effects On Herg1 and Rerg2mentioning
confidence: 94%
“…Procedures used for the surgical removal of ovarian lobes from Xenopus laevis and isolation of oocytes was approved by the University of Utah Institutional Animal Care and Use Committee and performed as described previously (Abbruzzese et al, 2010). Single oocytes were injected with 5-40 ng cRNA encoding WT or mutant ERG subunits and studied 2-7 days later.…”
Section: Methodsmentioning
confidence: 99%
“…Oocytes were enzymatically isolated from ovarian lobes excised from Xenopus laevis using procedures as described previously (Abbruzzese et al, 2010) and approved by the University of Utah Institutional Animal Care and Use Committee. Single oocytes were injected with 5-30 ng of hERG1 cRNA and incubated for 1-4 days before use in voltage-clamp experiments.…”
Section: Methodsmentioning
confidence: 99%